Does Money Relieve Depression? Evidence from Social Pension Expansions in China - Xi Chen; Tianyu Wang; Susan H. Busch (Global Labor Organization (GLO), 2018)
We estimate the impact of pension enrollment on mental well-being using China's New Rural Pension Scheme (NRPS), the largest existing pension program in the world. Since its launch in 2009, more than 400 million Chinese have enrolled in the NRPS. We first describe plausible pathways through which pension may affect mental health. We then use the national sample of China Family Panel Studies (CFPS) to examine the effect of pension enrollment on mental health, as measured by CES-D and self-reported depressive symptoms. To overcome the endogeneity of pension enrollment or of income change on mental health, we exploit geographic variation in pension program implementation. Results indicate modest to large reductions in depressive symptoms due to pension enrollment; this effect is more pronounced among individuals eligible to claim pension income, among populations with more financial constraints, and among those with worse baseline mental health. Our findings hold for a rich set of robustness checks and falsification tests.
Keywords: H55; I18; I38; J14; 330; pension enrollment; pension income; depression; mental health; older populations